Controlling effects of pore‐throat structure and fractal characteristics on the physical properties of ultra‐low permeability sandstone reservoirs: A case study of the sixth member of the Yanchang Formation in the Xiaojiahe area, Ordos Basin. Issue 5 (27th February 2023) - Li, Guoxiong; Liu, Chenglin; Zhou, Ya‐nan; Wu, Hanning; Awan, Rizwan Sarwar; Shi, Fei; Wu, Yunfei; Zang, Qibiao; Wu, Yuping
Abstract : Low and ultra‐low permeability reservoirs are widely developed in the Upper Triassic Yanchang Formation in the Ordos Basin, and its intricate pore throat structure has a significant impact on the physical properties and heterogeneity of reservoirs. This paper conducted a series of experiments to investigate the petrology, pore structure, fractal characteristics of ultra‐low permeability sandstone reservoirs, and influencing factors of the physical properties. The results show the sixth member of the Yanchang Formation (Chang 6) reservoir in the Xiaojiahe area is dominated by feldspathic sandstone. The main pores are intergranular pores, followed by dissolution pores. The Chang 6 sandstone has been categorized into four types (type I–IV) based on the traits of mercury intrusion curves. The high content of quartz and feldspar in the detrital components is conducive to improving the physical properties of the reservoir. The pore‐throat structure parameters, such as displacement pressure, median pressure, and pore throat radius can characterize the change in physical properties and reservoir quality. According to the capillary pressure fractal model of r apex (Pittman's plot apex radius), demonstrating the ultra‐low permeability, sandstone has a binary structure. The fractal dimensions D 2 and D p are more appropriate for characterizing the heterogeneity of the pore structure. The effects of different pore‐throat size scales on the physical properties of the reservoir have a discrepancy. Relatively large pore throats ( r  >  r apex ), non‐nanoscale pore throats (Por r >0.1 ), and effective movable pore throats (Porem ) have significantly positive control effects on permeability and reservoir quality. In contrast, the development of nanoscale pore throats (Por r <0.1 ) and micropore throats of failure to enter mercury (Porfem ) are unfavourable to reservoir performance. In conclusion, combining detrital components, pore‐throat structure, fractal characteristics, and other factors controlled the reservoir quality of ultra‐low permeability sandstone. Abstract : The ultra‐low permeability sandstone has a binary pore‐throat structure model. The small proportion of large pores significantly contributed to permeability. The non‐nanoscale pore throats and effective movable pore throats have a remarkable contribution to the infiltration capacity of ultra‐low permeability sandstone, which is the dominant factor of reservoir quality.